Formulasi Bioinsektisida Berbahan Aktif Metarrhizium anisopliae Isolat Lokal untuk Mengendalikan Hama Cylas formicarius pada Ubi Jalar - Nina Jeni Lapinangga (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2023)
One of the limiting factors for sweet potato productivity in the South Central Timor District is the Cylas formicarius pest attack. This control using synthetic pesticides can have a negative impact. One alternative pest control that can reduce these impacts is biological pest control. The use of bioinsecticides from entomopathogenic fungi on a wide scale needs to pay attention to the right formulation that can help in terms of availability, mass propagation, storage and application. This study aims to find an appropriate and effective formulation of Metarhizium anisopliae for mass production. The results of this study were a local isolate of the fungus M. anisopliae which was enriched with insect meal with a high virulence level. There are three types of formulations made and tested, namely pellet, flour, and liquid formulations. This study was arranged using a completely randomized design with 4 treatments and 4 replications. Data on fungal growth and pathogenicity were tested by means of variance and followed by the Least Significant Difference test at the 5% level. The results showed that the density of the conidia of M. anisopliae in the liquid formulation was significantly higher (10.31 x 109 /ml) compared to the alginate pellet formulation (8.65 x 109 /ml) and the flour formulation (8.65 x 109 /ml). The highest mortality was found in liquid formulations. This means that the liquid bioinsecticide made from M. anisopliae is the most virulent against C. formicarius larvae. Keywords: bioinsecticide formulation, entomopathogenic fungus, Metarhizium anisopliae.